PENERAPAN SENSOR GETAR DAN SENSOR SUHU UNTUK PEMANTAUAN MOTOR DC BERBASIS IOT - Fayyadhah, Filzan; Fitriani, Endah; Paramitha, Nina; Purwanto, Timur Dali (Rang Teknik Journal, 2025)
DC motors (Direct Current) have become a key component in various industrial applications and electronic devices. With technological advancements, monitoring and maintenance of DC motors have become increasingly important to ensure efficient operation and prevent unexpected failures. One way to enhance DC motor monitoring is by integrating RPM and temperature sensors, which can provide crucial information regarding the motor's operational conditions. This research aims to develop a tool for detecting the condition of DC motors by comparing temperature and motor speed variables. The components used in assembling this device include an IR Obstacle Sensor, Thermocouple Sensor, ESP32 Microcontroller, I2C LCD, and Servo. The working principle of this research tool involves connecting it to a 220V power source, then switching the ON/OFF switch. Once the device receives power, the sensors and other components will be ready, indicating that they are prepared to read the pre-programmed instructions. For testing the device, first, the DC motor is activated by setting the PWM value between 0-255. Then, the thermocouple sensor and RPM sensor will read the motor's condition when the DC motor is on, which will be displayed on the LCD. If the DC motor temperature exceeds 50°C, the LED will turn ON, indicating that the motor's temperature is above 50°C and providing information on the motor's speed.Keywords: ESP32, K-Type Thermocouple, RPM, DC Motor, IoT